2013
DOI: 10.2147/dddt.s40622
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a peptide-containing synthetic lung surfactant on gas exchange and lung mechanics in a rabbit model of surfactant depletion

Abstract: BackgroundCurrently, a new generation of synthetic pulmonary surfactants is being developed that may eventually replace animal-derived surfactants used in the treatment of respiratory distress syndrome. Enlightened by this, we prepared a synthetic peptide-containing surfactant (Synsurf) consisting of phospholipids and poly-l-lysine electrostatically bonded to poly-l-glutamic acid. Our objective in this study was to investigate if bronchoalveolar lavage (BAL)-induced acute lung injury and surfactant deficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Lucinactant is an SP-B-based synthetic surfactant composed of a phospholipid mixture and sinapultide, a leucine-and lysine-reach peptide aimed at mimicking SP-B function (17). Synsurf is a surfactant consisting of a phospholipids mixture and two polypeptides: poly-l-lysine electrostatically complexed with poly-l-glutamic acid (18).…”
Section: Introductionmentioning
confidence: 99%
“…Lucinactant is an SP-B-based synthetic surfactant composed of a phospholipid mixture and sinapultide, a leucine-and lysine-reach peptide aimed at mimicking SP-B function (17). Synsurf is a surfactant consisting of a phospholipids mixture and two polypeptides: poly-l-lysine electrostatically complexed with poly-l-glutamic acid (18).…”
Section: Introductionmentioning
confidence: 99%
“…The recently developed Synsurf was also tested earlier, in vivo in an adult rabbit saline-lavaged model 8. In that study, we showed significant improvement in oxygenation and pulmonary shunt in the group of animals treated with Synsurf.…”
Section: Discussionmentioning
confidence: 72%
“…Synsurf was prepared as described previously 8. Briefly, dipalmitoylphosphatidylcholine (DPPC), hexadecanol, and phosphatidylglycerol were mixed in a 10:1.1:1 ratio (w/w) in chloroform.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations